"Does serum estrogen level have an impact on outcomes in hormonal replacement frozen-warmed embryo transfer cycles?". (3rd October 2021) - Garimella, Sita; Karunakaran, Sandeep; Gedela, Durga Rao
Abstract: Aim: To evaluate the impact of serum estradiol (E2) levels on cycle outcomes in hormone replacement frozen embryo transfer (HR- FET) cycles. Materials and methods: We retrospectively analyzed 509 HR-FET cycles performed from September 2018 to September 2019. Patients were divided into 6 groups based on their E2 values measured a day before progesterone initiation . Group 1: <100 pg/mL, group 2: 100–200 pg/mL, group 3: 200 − 300 pg/mL, group 4: 300–400 pg/mL, group 5: 400–500 pg/mL, group 6: >500 pg/mL. Implantation rate (IR), clinical pregnancy rate (CPR), miscarriage rate (MR), multiple pregnancy rate (MPR) and ectopic pregnancy rates were compared between all groups. Results: IR and CPR were similar between a wide range of E2 values, but when E2 values were more than 500 pg/mL there was a non significant fall in the IR (47.3% vs 48.3% vs 48.6% vs 47.8% vs 48.7% vs 39.6% p = .77) and CPR (63.6% vs 65.1% vs 65.6% vs 65.3% vs 65.6% vs 53.1% p = .692). MR was significantly high when E2 was less than 100 pg/mL (28.5%) and when E2 was more than 500 pg/mL (41.1%) ( p = .02). MPR and ectopic pregnancy rates were similar between all the groups Conclusion: Outcomes of FET cycles were similar between a wide range of E2 values (100–500 pg/mL). When E2 levels were less than 100 pg/mL or more than 500 pg/mL there was significant increase in the MR but the numbers in these groups are less and further studies are required to confirm these facts.